1988
DOI: 10.1128/jb.170.4.1902-1906.1988
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of insertion sequence IS3411, which flanks the citrate utilization determinant of transposon Tn3411

Abstract: The nucleotide sequences of insertion sequences IS3411L (left) and IS3411R (right), present as direct terminal repeats in the citrate utilization of citrate utilization transposon Tn3411, and of IS3411 (generated by intramolecular recombination between IS3411L and IS3411R) were determined. The three IS3411 elements (IS3411R, IS3411L, and IS3411) were 1,309 base pairs long and identical in DNA sequence. IS3411 had 27-base-pair terminal inverted repeats with three bases mismatched and one long open reading frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Sequence analysis of IS911 indicates that it is a member of the IS3 group of elements (32,33). This analysis also revealed that IS3411 (12), IS476 (14), and ISRJ (29) belong to this group. The disposition of open reading frames and possible control of expression of transposition functions of IS911 and other members of the group are also discussed.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Sequence analysis of IS911 indicates that it is a member of the IS3 group of elements (32,33). This analysis also revealed that IS3411 (12), IS476 (14), and ISRJ (29) belong to this group. The disposition of open reading frames and possible control of expression of transposition functions of IS911 and other members of the group are also discussed.…”
mentioning
confidence: 90%
“…2 (33), and IS861 (32). Three additional elements, IS3411 (12), ISRJ (29), and IS476 (14), are also members of this group (see below). They exhibit a limited degree of similarity at the nucleotide sequence level (33) (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…This is the first reported case of which we are aware, however, of insertional inactivation of a gene by IS3411. IS3411 has been shown to constitute the ends of the composite transposon Tn3411, which encodes citrate utilization genes (16)(17)(18) (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Shown is the inverse complement of the actual sequence obtained. 17). The generation of cointegrates is believed to be evidence of replicative transposition.…”
Section: Methodsmentioning
confidence: 99%
“…The genes for citrate utilization are present in widely distributed plasmids (166). In some cases the genes reside in a transposon, Tn3411, flanked by two copies of IS3411 (167). Similarly, lac genes are carried by many plasmids, converting essentially lac-less bacterial species to lac+ (59,121,285); in some cases the lac genes reside in a transposon structure, as in Tn951 (59).…”
Section: Integrity Of Bacterial Species Versus Lateral Transfermentioning
confidence: 99%